THE DISTRIBUTION OF ALIPHATIC AMINES IN THE CLOUD POINT EXTRACTION SYSTEMS: UDC 543.2, 542.61, 661.183.1 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2008)
The influence of general hydrophobicity of the aliphatic amines on their distribution between the water and surfactant–rich phases at cloud point temperature was investigated. The possibility of the separation of amines on groups depending on their hydrophobicity was shown. The influence of the substrate and non-ionic surfactant concentration on the efficiency of the micellar-extraction of amines was investigated. The correlations between the efficiency of the extraction of amines and lyophilic properties of the surfactant-rich phase were made. The solvation free energy of the aliphatic amines and their molecular fragments at the interphase transfer was calculated.
Keywords: -